Study of the Influence of Stress Factors on Animals (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
According to numerous studies, it has been found that stress disrupts the work of almost all organs and systems of living organisms. physiological indicators characterizing the functional state of the cns in stress-resistant and non-stress-resistant animals in the norm and under immobilization stress also change. the article presents modern data on the influence of stress factors on animals.